The accuracy of soluble urokinase-type plasminogen activator receptor for the diagnosis of neonatal sepsis: a meta-analysis - Ma, Jinjin; Chen, Xinqing; Wang, Xiaoyan; Liang, Jiaojiao; Guo, Liyan; Su, Yan; Hao, Ling; Ren, Changjun (Frontiers in Medicine, 2023)
Background: Neonatal sepsis is one of major causes of morbidity and mortality in newborns. However, atypical clinical manifestations and symptoms make the early diagnosis of neonatal sepsis still a challenge. Relatively high serum soluble urokinase-type plasminogen activator receptor (suPAR) have been implicated as a diagnostic biomarker for adult sepsis. Therefore, the meta-analysis is intended to explore the diagnostic value of (suPAR) for neonatal sepsis. Methods: PubMed, Cochrane Library, Embase, Web of science, China National Knowledge Infrastructure, China Biological Medicine Disc and Wanfang databases were retrieved from inception to December 31st 2022, to collect diagnostic accuracy studies about suPAR for neonatal sepsis. Two reviewers independently screened the literature, extracted data and assessed the risk of bias in included studies by the QUADAS-2 tool. Then meta-analysis was performed using Stata 15.0 software. Results: A tool of 6 articles involving 8 studies were included. The results of the meta-analysis showed that the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio and diagnostic odds ratio were 0.89 [95%CI (0.83-0.93)] , 0.94 [95%CI (0.77-0.98)], 14 [95%CI (3.5-55.2)], 0.12 [95%CI (0.08-0.18)] and 117 [95%CI (24-567)], respectively. The under-the-curve (AUC) of summary receiver operator characteristic (SROC) curves was 0.92 [95%CI (0.90-0.94)]. Sensitivity analysis confirmed the stability of the results, and publication bias was not observed. Fagan’s nomogram results demonstrated clinical availability of the findings. Conclusion: Current evidence suggests that suPAR has potential diagnostic value for neonatal sepsis. Due to limited quality of the included studies, more high quality studies are needed to verify the above conclusion.